Pengaruh Penambahan Filler dan Suhu Pengeringan terhadap Kandungan Antioksidan pada Daun Physalis angulata yang Diperoleh dengan Ekstraksi Menggunakan Air Subkritik - Ratna Frida Susanti; Dessy Natalia (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Physalis angulata or ceplukan is a wild plant, typically grows in rice field, forest or yard. Before the planting season, farmers typically exterminate those plants. However, it was well known in folk medicine having bioactive compounds which can cure several diseases such as asthma, hypertension, boil etc. In this research, Physalis angulata extract can be obtained by extraction using subcritical water. Subcritical water was chosen as a solvent because it is nontoxic; abundant with adjustable polarity so can replace the toxic organic solvents such as methanol, ethanol, acetone etc.The objective of this research is to study the effect of filler type and concentration along with drying temperature to the total phenol, flavonoid and IC50 in Physalis angulata leaves extract. Filler was added to absorb water and make the powder form of extract. Two kinds of fillers were used, aerosil and microcrystalline cellulose (MCC). The concentration of filler was varied from 0-30 wt% for MCC and 0-15 wt% for aerosil. The oven drying temperature was varied from 40-60 oC. The results show that an addition of filler improved the total phenol, flavonoid and antioxidant activity.The higher the concentration of filler, the better the total phenol, flavanoid and antioxidant activity.In the presence of filler, the total phenol improved by 5.5  folds for addition of 30 wt% MCC and 3.3 folds for 15 wt% aerosil at drying temperature of 60oC. Total flavonoid improved by 7.6 folds for addition of 30 wt% MCC and 7.3 folds for 15 wt% aerosil above the same drying temperature. The higherdrying temperature leaded to shorter drying time which can protect antioxidant from deterioration.